PENGARUH PENDEKATAN INKUIRI TERHADAP KEMAMPUAN RETENSI SISWA PADA MATERI SIFAT KOLIGATIF LARUTAN KELAS XII IPA SMA MUHAMMADIYAH 2 PONTIANAK - Ratna Ratna; Cawang Cawang; Fitriani Fitriani (Jurnal Ilmiah Ar-Razi, 2016)
ABSTRACT This research is motivated by the students’ low retention ability as they feel difficult to understand the basic concepts of chemical materials, react the elements, and use the chemical formulas. As a result, the Chemistry learning outcomes of class XII Science students, SMA Muhammadiyah 2 Pontianak, are low, especially on the colligative property of solution swith the completeness score of 41.93%. This study aimed at finding out the influence of inquiry approach on the colligative property of solutions to the students’ retention ability. Using pre experimental design, this study employed all grade XII Science students of SMA Muhammadiyah 2 Pontianak. They were taken by using non-probability sampling method. The collecting data instruments were description test, questionnaire, observation and questionnaire sheets. The study revealed that the post test and the retest instruments were valid (1,0) and the questionnaire, observation and questionnaire sheets were considered usable. In addition, the try-out of posttest and retest were reliable at the coefficient of 0,73 and 0,66. The results of retention ability indicated that there was a retention of 99,35%. The results of effect size showed that the retention ability was 1,17 (37,90%). Further, the response of 35 students to the inquiry based-learning was 97,14% which means that inquiry based learning positively influences the students’ retention ability, and this score is considered very good.Keywords: retention ability, inquiry approach, colligative property of solutions